2016
DOI: 10.1111/ans.13425
|View full text |Cite
|
Sign up to set email alerts
|

Surgical ward round checklist: does it improve medical documentation? A clinical review of Christchurch general surgical notes

Abstract: Background: Poor documentation of medical notes and plans not only adversely affects patient management but also has medico-legal implications. A standardized ward round checklist (adhesive proforma sticker, PFS) was introduced at our institu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…Comprehensive WR checklists introduced in the past, when implemented, have been found to take on average 12 min per patient for completion [ 30 ]. A recent study by Alamri et al [ 68 ] proposed a modified proforma in order to improve documentation as well as serve as important prompts during fast-paced surgical ward rounds (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive WR checklists introduced in the past, when implemented, have been found to take on average 12 min per patient for completion [ 30 ]. A recent study by Alamri et al [ 68 ] proposed a modified proforma in order to improve documentation as well as serve as important prompts during fast-paced surgical ward rounds (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Key ingredients in surgical checklists include: patient details, members of the multidisciplinary team, bedside patient consultation, history and examination findings, review of drains/tubes/lines, charts and medical investigations, documentation, estimated discharge date and presence of relatives/relevant discussions (Fig. 5 ) [ 68 , 69 ]. Indeed with advances in electronic patient records, surgical ward round templates can be introduced to ensure standardization and optimization of patient care—variations of these proformas can then be adjusted to suit the specifics in each specialty.…”
Section: Resultsmentioning
confidence: 99%
“…31 Post-follow-up surgical ward round proforma also improves recording quality. 25 Dolan et al, confirmed the use of proforma in the emergency surgery ward. 32…”
Section: Discussionmentioning
confidence: 96%
“…24 Several studies have shown that case studies alone were not enough to eradicate the documentation errors. 25-29 In these studies, only specific problems with the recording of medical data have been investigated and few studies have been conducted on the education of residents and all aspects of documentation. Also there is a gap on training issues in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Checklists build good habits and improve work organization among resident physicians and young specialist physicians [7].…”
Section: Introductionmentioning
confidence: 99%